A muldimensional approach of the relationship between teleworking and employees well-being: Romania during the pandemic generated by the SARS-CoV-2 virus - Dumitru Miron; Monica Aureliana Petcu; Maria Iulia David-Sobolevschi; Radu Cezar Cojocariu (Amfiteatru Economic Journal, 2021)
The inclusion of the issue of well-being in the social space, by contextualizing the process in functions of reconfiguring working conditions is of significant interest for both employees and employers in win-win approach. The dynamical systems produce chaotic behavior amplified by specific nonlinear feedback mechanisms and irreversible irregularities. The pandemic generated by SARS-CoV-2 virus has determined the extension of the use of telework and the issue of the dichotomy related potential benefits/ disadvantages associated with it. The anomie of the society with multiple dysfunctions is potentiated by the individual anomie induced by anti-pandemic measures. The purpose of this study is to analyze the impact of telework on employee well-being, from the perspective of the theory of social production function, considering seven areas of evaluation, assessed on the basis of specific items. In order to collect the subjectively perceived information, we developed an opinion questionnaire. The information was processed using correlation analysis and regression analysis. We noticed there are some differences in the perception of well-being depending on the workplace and gender. There is a positive relationship between professional development and competences, job satisfaction, work-life balance, organizational climate and well-being, and a negative relationship between the emotional dimension, commitment, autonomy and well-being in the case of the telework.
Keywords: J01; J50; 330; telework; well-being; autonomy; commitment; job satisfaction; emotional dimension; the function of social production